Engineering interactive design using internet (phase II) / Andre Miller Matali and Jimmy Boniface Babai - Matali, Andre Miller; Babai, Jimmy Boniface (1998)
In these modern days, Internet is known as the cheapest and easiest way to explore from country to another country. Computer programmers become more competitive among each other to make the Web more attractive and interactive. Talking about interactive, Java is the perfect program for that. This is what are we doing now. The project that we are working right now was known as Applet programming. To create this program, we had to use Java Workshop2.0 in, which is the only workshop that you can build or compile and run your programs with. After you have run the program, you will see the result in the Appletviewer. To edit this Applet to html file, all you have to do is just click the Project's button then choose projectname.tmp.html and save it in the same directory as your homepage. The name of the file must be ending with filename.html . The best part of this program is secured and simple. There is no change for hacker to hack your program. Your program is totally protected. Besides, this program is understandable. Most of the classes and methods already develop in Java Workshop2.0 tool bars. It is up to you to decide what to do with it. We believe in future, the demand for Java programming will grow up, because of its portability, security, fast, object-oriented, high-performance and simple.